A catalyst and additive-free three-component reaction of highly electrophilic azides with cyclic ketones and cycloaliphatic amines. Synthesis of novel N-heteroaryl amidines. Issue 18 (4th May 2016) - Efimov, Ilya; Beliaev, Nikolai; Beryozkina, Tetyana; Slepukhin, Pavel; Bakulev, Vasiliy
Graphical abstract: Highlights: A novel three-component reaction of azides with ketones and amines has been found. Method for the synthesis of new N -heteroaryl amidines was elaborated. Sulfonyl azides are shown to react with endocyclic amines to form N -sulfonyl amidines. Abstract: Highly electrophilic 5-azido-1-methyl-4-nitro-1 H -imidazole and sulfonyl azides were demonstrated to react with alicyclic amines and cyclic ketones in the absence of any catalyst or additive to afford novel N -(4-nitroimidazol-5-yl)- or N -sulfonylamidines respectively. Based on single crystal X-ray analysis, a revision of the previously reported data of Gao and co-workers on the direction of the reaction of sulfonyl azides with endocyclic enamines was made. The reaction of 2, 6-diazidopyridine with an enamine, 4-(cyclohex-1-en-1-yl)morpholine, proceeded with cyclization of the azide moiety onto the pyridine CN bond to form an amidine bearing the tetrazolo[1, 5- a ]pyridine fragment.